A Brief Recap of Tips and Surgical Manoeuvres to Enhance Optimal Outcome of Surgically Placed Peritoneal Dialysis Catheters. (19th July 2012) - Frost, Jodie H.; Bagul, Atul
Abstract : Background . Peritoneal dialysis (PD) is an effective option of renal replacement therapy for ESRF, offering advantages over haemodialysis. Peritoneal dialysis catheter (PDC) placement is thought to be the key to successful PD and the economic advantages are lost if a patient switches to HD in the 1st year. This paper is a brief document elaborating a recap of published literature, looking at various surgical tips and manoeuvres to enhance optimal outcome of PDC placement. Methods . A search strategy assessing for access team, preoperative antibiotic prophylaxis, type of catheter, catheter exit site, intraoperative catheter trial, optimal time to commence PD, hernia repairs, number of cuffs, catheter-embedding procedures, rectus sheath tunnelling, laparoscopic fixing, omentopexy, omentectomy, the "Y"-Tec system, resection of epiploic appendages, adhesiolysis, a trained surgeon, and perioperative catheter care protocol was used looking at various databases. Findings . The complications of catheterrelated dysfunction can be reduced with advanced planning of access placement, immaculate surgery, and attention to catheter insertion techniques. Conclusion . The success of a peritoneal dialysis programme depends upon functional and durable long term access to the peritoneal cavity; this depends on placement techniques and competent surgeons and psychosocial support to the patient. The various technical tips and manoeuvres elaborated here should be considered options carried out to improve outcome and reduce catheter dysfunction.